Assessment of the factors affecting farmers' choice of the production system in urban and peri urban dairy production system in Addis Ababa milk shed - Tadesse, M.; Tegegne, Azage (Ethiopian Society of Animal Production, 2000)
In this study available genetic resources and breeding systems used by dairy farmers in urban and peri-urban dairy production systems in, Addis Ababa milk shed were assessed. Results of the study indicated that: about 57%, 31 % and 10% of secondary town, peri urban and intra-urban farmers like to have crossbred, pure temperate and high grade animals for dairy production respectively. Among pure temperate breeds about 77% of the farmers like to have Friesian breed. The choice of breeds was mostly determined by milk yield potential, (56%) followed by feed consumption combined with milk yield (17%). The remaining few farmers combine milk yield, quality and disease resistance. The types of mating, system in all production systems are both AI and NS. About 19%, 50% and 45% of intraurban, peri-urban and , secondary town, farmers, combine AI and NS respectively. AI alone is used by, 25%, 50% and 12% of secondary town peri-urban and intra-urban farmers, respectively. 69% of intra-urban, and 30% pf secondary town farmers use natural mating alone. The choices of mating types in most cases are determined by increased milk yield, availability of service and reproductive efficiency. Most of Intra-urban (67%) and secondary town (80%) used crossbreed sire for natural mating, while pure temperate sire is used by more of peri-urban (50%) and some of intra-urban and secondary town farmers. Few farmers use, grade sire for NS. From these farmers that use Al about 50% of intra-urban and secondary, town farmers need to have back-up bulls while using Al. The majority of intra-urban (60%) and few of secondary town (17%) farmers preferred semen from bulls selected at Kaliti. However, all of peri-urban and 40% of intra-urban farmers preferred imported semen and or semen from imported bulls. More than 50% of secondary town farmers have not shown any preference toward. the sources of semen. Most of infra urban farmers (> 75%) select good bull for milk production and reproductive efficiency based on previous offspring's performance. More than 50% of secondary town farmers combine offspring dam's and sister's performance to select bull. About 94% of intra-urban, 68% of secondary town and 50% of peri-urban farmers used dairy farm to get cash income from sale of milk. Few farmers keep dairy animals to get income and utilise resources and / or labor.